Logistic regression improvements for credit scoring development - Pravdin, Nikolai (2022)
The current Study investigates the impact of non-linear relationships between input variables during credit risk modeling. Particularly, it is meant to analyze the burden of variables’ non-linear behavior on the current modeling benchmark – Logistic regression – using some general set of retail clients’ data. The main focus done on application of alternative solutions to efficiently mitigate nonlinearity’s influence. Among them is well-known strong learner - Random Forest, as well as relatively new approach – Penalized Logit Tree Regression – a transparent and intuitive combination of Logit and Decision Trees. Mentioned methods are modeled on both the real-world data and specific simulated data with step-by-step description of the process. Finally, results are analytically compared using popular performance metrics like Gini Index and K-S statistic.